MICROSTRUCTURAL ANALYSIS AND MECHANICAL PROPERTIES OF LM6 ALLOY PROCESSED BY COOLING SLOPE CASTING - Salleh, Mohd Shukor; Mohamad Ishak, Nurul Naili; Safian, Mohd Azizul Hikmi; Yahaya, Saifudin Hafiz (Journal of Advanced Manufacturing Technology (JAMT), 2016)
In this study, LM6 aluminium alloy were processed by semisolid metal processing via cooling slope casting technique. The primary objectives of this study were to investigate the most effective cooling slope parameter that affect the globulization of LM6 alloy. The mechanical properties of the alloy after the process were also discussed. The microstructural characterization was done by optical microscope (OM) while for mechanical test; tensile test and hardness test were performed. Some of the cooling slope samples were subjected to T6 heat treatment and the effect of heat treatment was discussed. The results obtained reveals that cooling slope casting produce a non-dendritic structures compared to conventional casting. The results also revealed that at pouring temperature of 660°C and 300 mm cooling slope length, the LM6 alloy exhibits a spherical microstructural feature due to all dendritic structures were replaced by ɑ-Al globule and rosette. For mechanical properties, it showed that tensile strength and hardness value were increased significantly as it process by cooling slope casting as compared to conventional casting. After T6 heat treatment the tensile strength and Vickers hardness increased about 23% and 7% respectively for a sample poured at 660°C and 300 mm slope length in cooling slope casting.